Kadar kreatinin serum pasien diabetes mellitus tipe 2 pada kelompok usia 40 tahun keatas - Asri Jumadewi; Rahmayanti Rahmayanti; Farah Fajarna; Wiwik Emmi Krisnawati (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: Diabetes mellitus type 2 (DMT2) is the most common type of diabetes and affects more than 90% of people with diabetes. Increasing age causes changes in carbohydrate metabolism and insulin release, which is influenced by blood sugar and inhibits the release of sugar into cells because it is influenced by insulin. The risk of diabetes mellitus increases with age, especially at 40 years and above. It happens because of the increase in sugar intolerance in people aged 40 and above.Objectives: This study aims to determine the description of serum creatinine levels in patients with type 2 diabetes mellitus at the age of 40 years and above.Methods: The research design is cross-sectional with inclusion criteria, namely DMT2 patients aged 40 years and above, and conducting examinations at the Prodia clinical laboratory, Banda Aceh branch, from January to May 2022. Samples were taken by accidental sampling, totaling 59 people. Data were collected by interview and laboratory examination to measure creatinine levels using the automatic analyzer method. The reference value for serum creatinine examination in men is 0,7-1,3 mg/dl and in women 0,6-1,1 mg/dl. Data analysis was done descriptively.Results: DMT2 patients aged 40 years and above were predominantly male (55,9%), and the frequency based on age range was mainly between 56-65 years (37,3%). As many as 16,9% of DMT2 patients aged 40 years and over had increased serum creatinine levels, although there were also 83,1% normal creatinine levels.Conclusion: DMT2 patients aged 40 years and above are dominant in men compared to women; the increase in creatinine levels do not show such a high value.